Occupational census profiling tool for librarians in the Philippines - Taban, Katrina O. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
Addressing the lack of an official occupational census profiling tool for licensed librarians in the Philippines, this study identified the minimum set of questions needed for a comprehensive occupational census questionnaire which had been honed after taking into consideration response-specific and questionnaire design factors. Three cycles of questionnaire testing had been rolled out to a 42 participants through purposive sampling.